Non-Viral Delivery Systems to Transport Nucleic Acids for Inherited Retinal Disorders - Md Jobair Jony; Ameya Joshi; Alekha Dash; Surabhi Shukla (Pharmaceuticals)
Inherited retinal disorders (IRDs) represent a group of challenging genetic conditions that often lead to severe visual impairment or blindness. The complexity of these disorders, arising from their diverse genetic causes and the unique structural and functional aspects of retinal cells, has made developing effective treatments particularly challenging. Recent advancements in gene therapy, especially non-viral nucleic acid delivery systems like liposomes, solid lipid nanoparticles, dendrimers, and polymersomes, offer promising solutions. These systems provide advantages over viral vectors, including reduced immunogenicity and enhanced targeting capabilities. This review delves into introduction of common IRDs such as Leber congenital amaurosis, retinitis pigmentosa, Usher syndrome, macular dystrophies, and choroideremia and critically assesses current treatments including neuroprotective agents, cellular therapy, and gene therapy along with their limitations. The focus is on the emerging role of non-viral delivery systems, which promise to address the current limitations of specificity, untoward effects, and immunogenicity in existing gene therapies. Additionally, this review covers recent clinical trial developments in gene therapy for retinal disorders.